Antimicrobial food packaging prepared from poly(butylene succinate) and zinc oxide. (November 2016) - Petchwattana, Nawadon; Covavisaruch, Sirijutaratana; Wibooranawong, Sasinee; Naknaen, Phisut
Highlights: PBS was stiffer due to the strengthening effect derived from ZnO. Minimum inhibition content of ZnO was 6 wt%. With ZnO, T c of PBS decreased while T m remains unchanged. Maximum Zn 2+ migration was found in acetic acid. Zn 2+ was found to release over 15 days studied. Abstract: This article reports antibacterial activity, mechanical, thermal and physical properties of poly(butylene succinate) (PBS)/zinc oxide (ZnO) composite films for food packaging applications. The composite films were successfully prepared by using a blown film extruder at five ZnO levels ranging from 2 to 10 wt%. Under tension, PBS was stiffer due to the strengthening effect derived from rigid ZnO particles. However, the tear strength of the composite films was lower than the film without ZnO. Minimum ZnO content required to inhibit the Escherichia coli and the Staphylococcus aureus growths were observed at 6 wt% with the clear zone of 1.31 and 1.25 cm respectively. Thermal test results indicated the increased degree of crystallinity (Xc ) and the decreased crystallization temperature ( T c ) while the melting temperature ( T m ) remain unchanged. Loss modulus curves informed the reduction of the glass transition temperature ( T g ) of the film with ZnO at all concentrations. Release test indicated that Zn 2+ migrated over 15 days studied while the maximum migration was observed when acetic acid was used as a food simulant.